Phosphorus removal by wheat (Triticum aestivum) and Lamb’s quarters (Chenopodium album) as affected by method of fertilizer application and competition period - TANVEER, ASIF; AHMAD, RASHID; AYUB, MUHAMMAD; ALI, ASGHAR (The Indian Journal of Agricultural Sciences, 2013)
A field study comprising fertilizer application lind competition periods was conducted during 1992-94 using a split-plot design. Phosphorus concentration and its uptake by Lamb’s quarters (Chenopodium album L.) was signifi- cantly more in broadcast incorporate method than side placement. Wheat (Triticum aestivum L. emend Fiori & Paol.) showed high concentration and uptake of P in side placement. Maximum P concentration and its uptake by Lamb’s quarters was 1.12% and 1.24 kg/ha respectively in 6 weeks competition. Maximum phosphorus concentration and its uptake for wheat was 0.72% and 25.75 kg/ha at 5 weeks after emergence and in full season competition respectively.